Cinematic ghosts haunting and spectrality from silent cinema to the digital era - Leeder, Murray (Bloomsbury Academic, 2015)
"A collection of essays that explores the various roles ghosts have played in motion pictures, spanning a range of time periods, genres and nations"--
Bevorzugte Informationsquelle: Landingpage (Bloomsbury Collections), da weder Titelblatt noch Impressum vorhanden
Keywords: Geschichte; Ghosts in motion pictures; Supernatural in motion pictures; PERFORMING ARTS / Film & Video / History & Criticism; PERFORMING ARTS / Film & Video / General; Geister -- Motiv; Film; Aufsatzsammlung